Aeration effects on water-structure impacts: Part 2. Wave impacts on a truncated vertical wall. (15th August 2019) - Mai, T.; Mai, C.; Raby, A.; Greaves, D.M.
Abstract: Aeration effects on wave loading are of considerable importance for offshore design. This paper describes experimental work to investigate four types of wave impact on a truncated vertical wall (representative of a plate in an FPSO vessel), in pure and aerated water. Investigations showed that high aeration and flip-through wave impacts are the most severe impact types and should therefore be considered for offshore structure design. It was also observed that there is a significant reduction in peak impact loads (both pressure and force) for impacts in aerated water compared to those in pure water. However, there was almost no reduction in impulsive loadings in aerated water compared to those in pure water, and therefore maximum instantaneous loads may be conservative in the presence of aerated water, in the implementation for offshore structure design. This paper is a companion paper to "Aeration effects on water-structure impacts: Part 1. Drop plate impacts". Highlights: Aeration effects on wave impacts have been experimentally investigated by means of wave impacts on a truncated vertical rigid wall in pure and aerated water. Significant reduction in the peak impact loads (both pressure and force) due wave impact from pure water to aerated water. The high aeration and flip-through wave impacts are the most severe impact types and they should be considered for offshore structure design. Post-impact, high frequency oscillations of pressures under wave impacts are due to repeated compression and expansion of the trapped air between wave front and the truncated wall. Maximum instantaneous loads may be conservative in the presence of aerated water in the implication for offshore structure design. Aeration effect is particularly important for offshore structures, where wave breaking is commonplace, leading to aerated wave interactions with structures.